RESPON DOSEN TERHADAP KEBIJAKAN IMPLEMENTASI KURIKULUM 2013 DI SEKOLAH/MADRASAH: (Studi Pada Dosen FTIK IAIN Palu) - Arifuddin M. Arif; Titin Fatimah (ISTIQRA, 2016)
According to the national context, the policy of education curriculum change is political related to the interests of the stakeholders including Universities. Faculty of education and Teacher Science IAIN Palu as providers of education personnel are required to prepare prospective teachers who have an understanding of conceptual and implementable technique to Curriculum 2013. What degree of achievement of competencies of graduates who master the concepts and techniques of learning curriculum implementation in 2013, it is also determined by how much the level of understanding and control of lecturers conceptually and technically implementable on the 2013 curriculum that will be taught to students. Therefore, a responsibility FTIK lecturer in the curriculum policy implementation in 2013 is now a necessity. Reinforcement learning materials Curriculum 2013 lecturer with the perspective of any sort is indispensable model. Model reinforcement learning materials perspective, the 2013 curriculum can be developed in the form of "concurrent model", ie the lecture, learning material substance, and the substance of the teaching profession throughout the course of relevant perspectives always in conjunction with Curriculum 2013. Meaning of lecture material is given in conjunction with the material which forms the teachers teaching in the school / madrasah, especially those based learning curriculum, 2013. So the students as future teachers "ready-made" and responsive and adaptive to the development of education and learning in the school / madrasah